INOVASI DIGITAL DALAM PELAYANAN KARTU IDENTITAS ANAK DI KOTA PADANG - Nila Wahyuni (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to examine the adoption of digital innovation through the utilization of the Sirancak system in the provision of child identity card services in Padang City. The research employed a descriptive qualitative research methodology. The study was carried out from January to March of the year 2023. This study encompassed interviews with 12 participants, comprising parents or guardians of children using the Sirancak system to issue child identity cards. Additionally, employees from the Population and Civil Registration Office of Padang City, who play a role in the implementation of the Sirancak system, were also included in the interviews. Data on participants' experiences, attitudes, and satisfaction with the services offered by the Sirancak system were gathered through interviews. This study demonstrates that implementing the Sirancak system enhances service efficacy by facilitating the accessibility and processing of information about issuing child identity cards. The study also showed that implementing the Sirancak system yields improved accessibility for the community. This digital platform enables individuals to submit applications for a child identity card remotely, eliminating the need for in-person visits to the service office. In summary, this study enhances our comprehension of the advantages associated with digital innovation in child identity card services.